First in-human PET study and kinetic evaluation of [18F]AS2471907 for imaging 11β-hydroxysteroid dehydrogenase type 1. Issue 4 (April 2020) - Bhatt, Shivani; Nabulsi, Nabeel B; Li, Songye; Cai, Zhengxin; Matuskey, David; Bini, Jason; Najafzadeh, Soheila; Kapinos, Michael; Ropchan, Jim R; Carson, Richard E; Cosgrove, Kelly P; Huang, Yiyun; et al.
11β-Hydroxysteroid dehydrogenase type 1 (11β-HSD1) catalyzes enzymatic conversion of cortisone into the stress hormone cortisol. This first-in-human brain imaging study characterizes the kinetic modeling and test–retest reproducibility of [ 18 F]AS2471907, a novel PET radiotracer for 11β-HSD1. Eight individuals underwent one 180-min ( n = 4) or two 240-min ( n = 4) [ 18 F]AS2471907 PET brain scans (12 total) acquired on the high-resolution research tomograph (HRRT) scanner with arterial blood sampling. Imaging data were modeled with 1-tissue (1T) and 2-tissue (2T) compartment models and with multilinear analysis (MA1) to estimate [ 18 F]AS2471907 availability ( V T ). [ 18 F]AS2471907 demonstrated high, heterogeneous uptake throughout the brain. Of the compartment models, 2T best described [ 18 F]AS2471907 data. Estimates of V T were highly correlated between 2T and MA1 ( t* = 30 min) with MA1 yielding V T values ranging from 3.2 ± 1.0 mL/cm 3 in the caudate to 15.7 ± 4.2 mL/cm 3 in the occipital cortex. The median absolute test–retest variability of 16 ± 5% and high intraclass correlation coefficient (ICC) values of 0.67–0.97 across regions indicate fair test–retest reliability but large intersubject variability. V T estimates using 180 min were within 10% of estimates using full acquisition time. In summary, [ 18 F]AS2471907 exhibits reasonable kinetic properties for imaging 11β-HSD1 in human brain.